Welding craft practice - Parkin, N.; Flood, C. R. (Pergamon international library of science, technology, engineering, and social studies., 1979)
Welding Craft Practice, Volume 1: Oxy-acetylene Gas Welding and Related Studies, Second Edition covers the ground necessary for the acquisition of the essential basic skills and safe working methods and sufficient technology in oxy-acetylene gas welding and related studies. Weld defects, testing of welds, and welding science are discussed, and a graduated series of practical exercises is included. This volume is comprised of five chapters and begins with an overview of the basics of oxy-acetylene gas welding, including the gases used (acetylene and oxygen, welding systems and equipment, and sa.